2016 IEEE 57th Annual Symposium on Foundations of Computer Science (FOCS) 2016
DOI: 10.1109/focs.2016.22
|View full text |Cite
|
Sign up to set email alerts
|

Hopsets with Constant Hopbound, and Applications to Approximate Shortest Paths

Abstract: A (β, ǫ)-hopset for a weighted undirected n-vertex graph G = (V, E) is a set of edges, whose addition to the graph guarantees that every pair of vertices has a path between them that contains at most β edges, whose length is within 1 + ǫ of the shortest path. In her seminal paper, Cohen [Coh00, JACM 2000] introduced the notion of hopsets in the context of parallel computation of approximate shortest paths, and since then it has found numerous applications in various other settings, such as dynamic graph algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
197
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(198 citation statements)
references
References 31 publications
1
197
0
Order By: Relevance
“…7 More precisely, following Elkin and Neiman [EN16], one constructs an overlay network of size √ sn instead of √ n as done in this paper. and for a node and set of nodes A ⊆ V by d(u, A, R,G) = min ∈A d(u, , R,G).…”
Section: Notationmentioning
confidence: 99%
“…7 More precisely, following Elkin and Neiman [EN16], one constructs an overlay network of size √ sn instead of √ n as done in this paper. and for a node and set of nodes A ⊆ V by d(u, A, R,G) = min ∈A d(u, , R,G).…”
Section: Notationmentioning
confidence: 99%
“…In addition, we show that the superclustering and interconnection steps themselves can be implemented efficiently. This part of the algorithm is based on our recent work on hopsets [34], where we showed that [35] approach is extremely useful in that context as well, and that it can be made efficient.…”
Section: Technical Overview Linial and Saksmentioning
confidence: 99%
“…In some cases, different edges of the graph may have different attributes, which can be represented using edge weights. The existence of edge weights has been extensively studied in various tasks, such as finding or approximating lightest paths [20,37,27,21,34,31,4,25], finding a minimum spanning tree (MST) in the graph [5,23,13], finding a maximum matching [36,13], and more. However, as far as we are aware, no study addresses the problem of constructing multiple weighted BFS (WBFS) trees, where the goal is not to find the lightest paths from the sources to the nodes, but rather the lightest shortest paths.…”
Section: Introductionmentioning
confidence: 99%